2016
DOI: 10.1101/082289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual dimorphism in gene expression and regulatory networks across human tissues

Abstract: SummarySexual dimorphism manifests in many diseases and may drive sex-specific therapeutic responses. To understand the molecular basis of sexual dimorphism, we conducted a comprehensive assessment of gene expression and regulatory network modeling in 31 tissues using 8716 human transcriptomes from GTEx. We observed sexually dimorphic patterns of gene expression involving as many as 60% of autosomal genes, depending on the tissue. Interestingly, sex hormone receptors do not exhibit sexually dimorphic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…Studying the transcriptome is a very powerful hypothesis-free approach to elucidate the molecular mechanisms underlying diseases and phenotypes. In this study, we analyzed the differential transcriptomics of human airway epithelium at baseline and in response to smoking between males and females u. and found that 1) smoking has a large and reproducible effect on sexually dimorphic gene expression were noted in the breast, skin, thyroid, brain, and adipose tissues while the least dimorphic was the gastrointestinal tract 18 . Multiple other studies in single cell or tissue types have confirmed to varying extents the large transcription differences between the two sexes [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Studying the transcriptome is a very powerful hypothesis-free approach to elucidate the molecular mechanisms underlying diseases and phenotypes. In this study, we analyzed the differential transcriptomics of human airway epithelium at baseline and in response to smoking between males and females u. and found that 1) smoking has a large and reproducible effect on sexually dimorphic gene expression were noted in the breast, skin, thyroid, brain, and adipose tissues while the least dimorphic was the gastrointestinal tract 18 . Multiple other studies in single cell or tissue types have confirmed to varying extents the large transcription differences between the two sexes [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…MEF2C is also a known downstream target of the androgen receptor (AR), thus making it highly susceptible to androgen-dependent transcriptional influence 43 . MEF2C is also one of the most important transcription factor genes influencing sex differences in human brain gene expression -MEF2C differentially targets genes as a function of sex, and the magnitude of this sex-differential targeting explains a large percentage of variance in sex differences in gene expression of its putative targets 44 . Our work further underscores MEF2C's involvement in male-specific mechanisms behind atypical neurodevelopment, and particularly highlights how MEF2C could be one of many candidates behind fetal programming effects of androgens on developing social brain circuits such as the DMN.…”
Section: Discussionmentioning
confidence: 99%
“…MEF2C is also known to be a downstream target of the androgen receptor 43 . As a transcription factor itself, MEF2C is also known to differentially target other genes as a function of sex and the degree of such sex-differential targeting explains a substantial amount of variance in sex-differential expression 44 . Confirming DHT-upregulation of MEF2C expression we ran a follow-up experiment using qPCR and found that indeed the upregulation of MEF2C by DHT in the RNA-seq data is replicated using qPCR on three additional independent cell lines and (t = 3.73, p = 0.003, replication Bayes Factor = 164) ( Figure 3B-C).…”
Section: Figure 2: Synaptic Enrichments Of Dht-dysregulated Genes Andmentioning
confidence: 99%
“…al. (34), which were modeled on data from the Genotype-Tissue Expression (GTEx) project (35). For the colon cancer networks, we reconstructed gene regulatory networks for each sample as shown in Figure 1.…”
Section: Differential Targeting Of Biological Pathways In Males and Fmentioning
confidence: 99%